The growth of the Japanese black tea market: How technological innovation affects the development of a new market - Risa Takano; Daisuke Kanama (Journal of Economic Structures, 2019)
This paper studies the birth of the market for Japanese black tea, its decline, and its rebirth. Currently, the black tea consumed in Japan is mostly imported. But the production of Japanese black tea has gradually increased, and more than 200 tons was produced in 2016. We investigate the history of Japanese black tea, the use of manufacturing technology, and the components of tea and their effects on humans to influence quality. We found the main reasons for the revival and spread of Japanese black tea were production and manufacturing innovation. Fermentation was especially an important process because it determined tea quality. Manufacturing technology for fermentation was established by entrepreneurial farmers and transferred to other Japanese black tea farmers, resulting in the rapid market creation of the Japanese black tea.
Keywords: 330; Japanese black tea; New market; Entrepreneurship; Japanese green tea; Technological innovation